Pulmonary artery augmentation and aortic valve repair using novel tissue-engineered graftsCentral MessagePerspective - Hisayuki Hongu, MD, PhD; Masaaki Yamagishi, MD, PhD; Keiichi Kanda, MD, PhD; Yoshinobu Maeda, MD; Tomoya Inoue, MD, PhD; Hiroki Nakatsuji, MD, PhD; Hitoshi Yaku, MD, PhD (JTCVS Techniques)
Objectives: The objectives of this study were to evaluate the results when tissue-engineered vascular grafts (TEVGs) are used as alternatives to autologous pericardium for surgically augmenting the pulmonary artery (PA) or aortic valve. Methods: TEVG molds were embedded into subcutaneous spaces for more than 4 weeks preoperatively. Since 2014, 6 patients have undergone PA reconstruction, whereas 1 has undergone aortic valve plasty (AVP) with TEVGs. The time from mold implantation to the operation was 8.9 (range, 6.0-26.4) months. The age and body weight at the time of operation were 2.7 (range, 1.8-9.2) and 11.6 (range, 7.9-24.4) kg, respectively. Concomitant procedures comprised the Rastelli, palliative Rastelli, and Fontan operations in 2, 2, and 1 patient, respectively. Results: The median follow-up period was 14.4 (range, 3-39.6) months. There were no early or late mortalities. Moreover, there were no TEVG-related complications, including aneurysmal changes, degeneration, and infection. In 5 patients who underwent PA augmentation, the postoperative PA configuration was satisfactorily dilated. The reconstructed aortic valve function was good in the patient who underwent AVP. Decreased leaflet flexibility due to leaflet thickening was not observed. One patient had postoperative PA re-stenosis; therefore, re-PA augmentation with TEVGs was performed. On histological examination, TEVGs consisted of collagen fibers and few fibroblasts, and elastic fiber formation and/or smooth muscle cells were not observed. Conclusions: The midterm results of PA reconstruction and AVP with TEVGs were satisfactory. TEVGs might be a useful alternative to autologous pericardium in pediatric cardiovascular surgeries that often require multistage operations.